การพัฒนาตัวบ่งชี้การเรียนรู้ตลอดชีวิตของพลเมืองไทยด้วยกระบวนการมีส่วนร่วมของชุมชน - ศรัญญา รณศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
The study applied a mixed method design. Objectives were to: 1) develop indicators to measure lifelong learning for Thai citizens using community participation process; 2) validate and assess the quality of developed indicators using community participation process; and 3) develop a manual for delivering developed lifelong learning indicators to practices. A qualitative study was conducted using community participation process from six communities, including 1) Ban Nong No, Saraburi, 2) Ban Dan Singkhon, Prachuap Khiri Khan, 3) Kiriwong Village, Nakhon Si Thammarat, 4) Ban Chi Thuan, Ubon Ratchathani, 5) Ban Choeng Doi, Chiang Mai, and 6) Khao Yaida Community, Rayong. A quantitative study was conducted with a sample of 4,828 participants. The results were as follows: 1. The lifelong learning indicators for Thai citizens consist of five dimensions: 1) attitudes towards learning - awareness, importance and essence of learning, learning happiness, self-improvement need, and continuous learning. 2) skills and abilities to learn - Thai language proficiency, literacy, basic computational skill, foreign language skill, digital literacy, communication skill, and problem-solving skill. 3) self-directed learning skills – personal goal setting and learning plan, selecting self-directed learning method, self-responsibility and reliance, asking a right question, effectively searching of information online, being able to prioritize what to learn and summarize, and applying knowledge. 4) learning behaviors – being curious for learning, discipline, being thoughtful, ability to cope with change, being creative, being responsible to learn, having learning goal, supporting and helping others to learn. and 5) beneficial knowledge for lifelong learning. – general knowledge of health, nature, and environment related topics, understanding community context, community cultural and traditional competence, professional knowledge and skill, understanding civil rights and social welfare, ability to apply past knowledge to new situations, knowledge seeking ability, ability to continually increase their knowledge, being flexible, and skill development and capacity building. 2. The indicators developed with the content validity, the reliability of 0.94 and a discriminatory power value of 0.36 to 0.80. Developed model of lifelong learning indicators for Thai citizens fitted the empirical data. The factor loadings of indicators were all statistically significant (p < .01). A self-directed learning skill was weighted as the most important indicator, following by learning behaviors, skills and abilities to learn, beneficial knowledge for lifelong learning, and attitudes towards learning, which was of the least important indicator. 3. The manual for delivering developed lifelong learning indicators to practices consists of: 3.1) the measurement of lifelong learning levels consists of the lifelong learner of Thai citizens assessment and the Criterion-referenced interpretations of lifelong learning score of Thai citizen and 3.2) supporting and promoting guidelines to become a lifelong learner